2009
DOI: 10.22358/jafs/66393/2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing malate and yeast culture (<i>Saccharomyces cerevisiae</i>) on the rumen enzyme profile and growth performance of lambs

Abstract: The objectives of this study were to determine the effects of adding a mixture of malate and yeast culture (Saccharomyces cerevisiae) on cellulolytic, amylolytic, proteolytic and ureolytic activity in the rumen and on the growth performance of lambs. Eight native breed (Lory-Bakhtiary) lambs aged approximately 7 months (four males and four females) were divided into two groups by sex. They were kept in individual pens and fed a total mixed ration (TMR) based on lucerne hay-wheat straw and concentrate. The two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
4
10
1
1
Order By: Relevance
“…Such activity depends rather on the number and activity of amylolytic bacteria, but these were not monitored in this study. In contrast to our result, Moharrery and Asadi (2009) found a positive effect of yeast on the activity of amylolytic enzymes in the rumen of lambs. In contrast, Brossard et al (2006) and Kowalik et al (2008) did not observe any effect of yeast on the mentioned activity.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Such activity depends rather on the number and activity of amylolytic bacteria, but these were not monitored in this study. In contrast to our result, Moharrery and Asadi (2009) found a positive effect of yeast on the activity of amylolytic enzymes in the rumen of lambs. In contrast, Brossard et al (2006) and Kowalik et al (2008) did not observe any effect of yeast on the mentioned activity.…”
Section: Resultscontrasting
confidence: 99%
“…Both activities increased significantly when the control rations were enriched either with live Saccacharomyces cerevisiae or with its metabolites. These results are in agreement with the findings of Moharrery and Asadi (2009) who reported that the activity of cellulase increased in the rumen of lambs fed a mixture of malate and Saccharomyces cerevisiae yeast. The higher activity of xylanase in animals fed live yeast agrees with results published by Michalet- Doreau et al (1997).…”
Section: Resultssupporting
confidence: 93%
“…In contrast, yeast metabolites significantly decreased cellulolytic activity compared with heifers fed the control diet only at 8 h after feeding. This is in agreement with the results of Moharrery and Asadi (2009), who reported that the activity of cellulase increased in the rumen of sheep fed a combination of malate and live S. cerevisiae. Moreover, ElWaziry and Ibrahim (2007) reported that the in vitro activity of cellulase was enhanced by the addition of yeast cells during 4 h incubation.…”
Section: Resultssupporting
confidence: 93%
“…Supplementation of live yeast, Saccharomyces cerevisiae, and its metabolites to diets improves productivity in ruminants (Moharrery and Asadi, 2009). The beneficial effect of these additives has been associated with their ability to alter rumen fermentation and stimulate microbial growth.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects are associated with increased milk production and improved performance of ruminants (Abd-El-Ghani, 2004;Moharrery and Asadi, 2009). Several hypotheses concerning the mode of action of yeast supplementation in ruminant nutrition have been proposed, but most of them emphasize positive effects achieved by modifying rumen fermentation.…”
Section: Introductionmentioning
confidence: 99%